- #1

- 15

- 0

thank you

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter thecoop
- Start date

- #1

- 15

- 0

thank you

- #2

- 6,054

- 391

(x' - x)t + x = 0

Let u = xt and the equation becomes

u' = u

If that fails, you can always convert an equation to an autonomous system of two equations in two variables, letting the second variable = time.

Share: